Unveiling Budgetary Slack: How Internal Control Systems Mediate the Effects of Competence and Whistleblowing - Lia Rachmawati; Diana Dwi Astuti; Muhammad Rijalus Sholihin; Inneke Putri Widyani; Norita Citra Yuliarti (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2026)
This study examines the effect of village apparatus competence and whistleblowing on budgetary slack, with the internal control system serving as a mediating variable. Employing a quantitative research design, the study applies the Structural Equation Modeling–Partial Least Squares approach to test both direct and indirect relationships among the variables. The sample for this study was determined using a census approach, encompassing all 226 villages in Jember Regency. Primary data were obtained through a structured questionnaire administered to a designated village official serving as a key informant, specifically those responsible for budgeting and financial management at the village level.  The results indicate that the village apparatus competence and whistleblowing positively affect the effectiveness of the internal control systems.  At the same time, both variables exert a negative effect on budgetary slack. Furthermore, the internal control systems negatively affect budgetary slack and partially mediate the relationships between village apparatus competence, whistleblowing, and budgetary slack. Theoretically, this study extends the Goal-Setting Theory by demonstrating that the alignment between budgetary objectives and actual outcomes in village governments depends on the integration of individual competence and ethical reporting mechanisms through an effective internal control system. Practically, the findings provide evidence-based insights for strengthening village financial governance through capacity building, robust internal controls, and accessible whistleblowing mechanisms.